ATHEROSCLEROTIC PLAQUE OF RENAL VASA RECTA ON PATIENT WITH CALCIUM STONE - Pramod, Sawkar Vijay; Sugandi, Suwandi; Sihombing, Aaron T.; Makmuri, Makmuri (Indonesian Urological Association, 2013)
Objective: We would like to identify whether atherosclerotic plaque inside renal vasa recta correlates with the formation of calcium stone. Material & Method: Samples are taken from kidney tissue removed by nephrectomy due to stone and non-stone disease. Histopathological examination with specific staining was performed by a single pathologist to find the atherosclerotic plaques inside the renal vasa recta. The result of each group was compared, and then analyzed using the Chi square test/Fischer exact test (SPSS ver.16.0; p < 0,05). Results: We found that the risk of calcium lithiasis is two-fold higher in the group with atherosclerotic plaques inside the renal vasa recta. (PR = 2,15; p < 0,05). Conclusion: Calcium stone are more likely to occur on patients with renal vasa recta atherosclerotic plaque, as possible sequelae of vascular injury.Keywords: Atherosclerotic plaque, vasa recta, calcium renal stone.